2006
DOI: 10.1007/s00040-006-0868-7
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia in the invasive European paper wasp Polistes dominulus

Abstract: The European paper wasp Polistes dominulus has been expanding its North American range since its introduction in the 1970s. We screened P. dominulus from Italy and the northeastern U.S. for the presence of the intracellular reproductive symbiont Wolbachia. Infection rates among females varied from 16 % to 87 % among U.S. sites and from 33 % to 71 % in Italy. We also found infected haploid and diploid males, indicating that this is not a male-killing Wolbachia infection. Our data show that infected individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Typically, within a host species, a single strain is associated with one or a set of similar mitotypes, and divergent strains are linked to different mitotypes, excluding recent Wolbachia horizontal transfer (Jiggins 2003; Shoemaker et al . 2004; Stahlhut et al . 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, within a host species, a single strain is associated with one or a set of similar mitotypes, and divergent strains are linked to different mitotypes, excluding recent Wolbachia horizontal transfer (Jiggins 2003; Shoemaker et al . 2004; Stahlhut et al . 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that broadly explored Wolbachia and mitochondrial variation among infected populations found that the two genomes are generally in linkage disequilibrium (Hurst & Jiggins 2005). Typically, within a host species, a single strain is associated with one or a set of similar mitotypes, and divergent strains are linked to different mitotypes, excluding recent Wolbachia horizontal transfer (Jiggins 2003;Shoemaker et al 2004;Stahlhut et al 2006). However, other studies have found instances of deviation from strict co-evolution between Wolbachia and mtDNA.…”
Section: High Contribution Of Horizontal Vs Vertical Transmission Wimentioning
confidence: 99%
“…Without further study of the system in this area, it is difficult to determine why there were so few C. pseudogracilis. Indeed, low sample numbers in the native range did not preclude Stahluhut et al (2006) from demonstrating that Wolbachia infection prevalence in invasive and Table 4. Further causes of decline may include general changes in the habitat over time, recent environmental disturbances, changes in pest (in particular mosquito) management, or even the result of a feminising microparasite driving local populations to extinction (Hatcher et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly the prevalence of the intracellular bacterial symbiont Wolbachia is similarly high in the native and introduced range of P. dominulus (Stahlhut et al . ), suggesting that this vertically transmitted bacterium has been co‐introduced with its host. The high prevalence of Wolbachia in both ranges could indicate low fitness costs associated with infection in this host species (Hurst et al .…”
Section: Parasite Release In Invasive Insect Societiesmentioning
confidence: 99%
“…Moreover, the Strepsiptera parasitoid, Xenos pallidus infecting the native Polistes fuscatus in the introduced area are not yet adapted to P. dominulus (Pickett & Wenzel 2000;Gamboa et al 2004). Interestingly the prevalence of the intracellular bacterial symbiont Wolbachia is similarly high in the native and introduced range of P. dominulus (Stahlhut et al 2006), suggesting that this vertically transmitted bacterium has been co-introduced with its host. The high prevalence of Wolbachia in both ranges could indicate low fitness costs associated with infection in this host species (Hurst et al 1999).…”
Section: Parasite Release In Invasive Insect Societiesmentioning
confidence: 99%